Bibliometric study on nanoscience and nanotechnology in Mexico based on Web of Science - Trujillo-Cancino, Jose Luis; Limaymanta, Cesar H. (Revista General de Información y Documentación, 2023)
It is evident that the nanosciences and nanotechnologies field will have a significant impact on various fields of action and will be linked to the development of a country, so their study is fundamental; On the other hand, the amount of information generated today makes it difficult to study a scientific topic. Therefore, information analysis tools are needed, both methodological and technological; in this context, metric methodologies are adequate to study a scientific field like this; Therefore, the present work aims to carry out a bibliometric study on the development of nanoscience and nanotechnology in Mexico based on the use of scientific mapping. Documentary analysis and the use of metric indicators of activity and relational indicators were used as methods and procedures. In the practical case, the data was taken from the Web of Science Database and Bibliometrix was used to develop the scientific-technological maps. We retrieved 15,876 research articles on N&N published between 1975 and 2021. The experimental results showed that they received an average of 17.61 citations per article, which were written in 2567 journals, more than 98% of the articles are written in English, and as for authors there is an average of 5.66 by document.
Keywords: Information bibliometric studies – Maps; Bibliometric Maps; Science Maps; Mexico; Bibliometric Studies; Nanoscience; Bibliometric studies; Nanotechnology